Shortlist Top Tens - Publishe by Collins (London Collins, 2009)
For men with more than one thing on their minds We love lists! Here are the top 10 things to do with ShortList Top Tens: 1) Buy it 2) Open it and be amazed by its sleek design and creativity 3) Read it and find over 300 Top Tens and pages of fascinating trivia 4) Discover the top 10 weird things MPs spend our money on 5) Share your knowledge of the top 10 restaurants in the world with a female of the species - she'll be so impressed you won't even need to take her to one 6) Visit the top 10 websites that you just can't live without 7) Settle that debate with your mates about which sci-fi vehicle is the best - and no, it isn't The Enterprise 8) Nearly leave it in the pub on quiz night 9) Marvel at the antics of the top 10 harshest art critics on the planet 10) Love it
Include Illustrations and Index
Keywords: Curiosities and wonders